2003
DOI: 10.1002/tcm.10062
|View full text |Cite
|
Sign up to set email alerts
|

Natural dietary agents can protect against DMBA genotoxicity in lymphocytes as revealed by single cell gel electrophoresis assay

Abstract: Many natural agents including fruits and vegetables are known to provide protection from different degenerative diseases including cancer, by preventing damage to the cellular components. The effect of two important dietary agents, alpha tocopherol, and the flavonoid quercetin, along with two commonly consumed vegetables, bitter gourd and tomato, were investigated on spontaneous and dimethylbenz(a)anthracene (DMBA)-induced DNA damage in murine lymphocytes in vitro. DNA damage was determined by single cell gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Approximately 75% of the world’s populations depend on CAM as reported by the world health organization reports ( Grawish et al, 2010 ). Several natural products has been suggested to be beneficial for reducing DMBA toxicity including hops, rosemary, cat's claw ( El Kholy et al, 2013 ) and bitter gourd and tomato ( De et al, 2003 ). Bovine colostrum (BC) has been known and used for years in the treatment of infectious diseases in humans ( Struff and Sprotte, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 75% of the world’s populations depend on CAM as reported by the world health organization reports ( Grawish et al, 2010 ). Several natural products has been suggested to be beneficial for reducing DMBA toxicity including hops, rosemary, cat's claw ( El Kholy et al, 2013 ) and bitter gourd and tomato ( De et al, 2003 ). Bovine colostrum (BC) has been known and used for years in the treatment of infectious diseases in humans ( Struff and Sprotte, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…MC pulp and seed powders exhibit stronger anti-oxygenic activity than other solvent extracts, while MC pulp and its extracts show slightly higher anti-oxygenic activity than MC seed and its extracts [107] . De et al have found that fresh juices of MC and tomato could also protect from DMBA-induced DNA damage, but not as effectively as the single agents [108] .…”
Section: Introductionmentioning
confidence: 99%
“…To date there is no evidence in literature that investigate the effect of quercetin on both genomes. A lot of data are available regarding the quercetin effect on nuclear DNA by measuring nonspecific DNA damage by comet assay [8,[14][15][16]18,20,29,32,40,[48][49][50][51][54][55][56]59]. This technique, however, though sensitive, fast and easy, highlights only damages in terms of break of single or double strand of nuclear DNA.…”
Section: Discussionmentioning
confidence: 99%